2016
DOI: 10.1016/j.chom.2016.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Human Microbiota-Associated Mice: A Model with Challenges

Abstract: Human microbiota-associated (HMA) mice have been used extensively in gut microbiome research. Here we discuss ecological and evolutionary aspects of the mammalian-gut microbiome interrelationship that confound the application of HMA mice, and propose experimental designs that increase the likelihood for obtaining meaningful findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
173
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(177 citation statements)
references
References 15 publications
3
173
0
1
Order By: Relevance
“…Despite the momentum provided by preclinical microbiome studies, there is a growing appreciation of the challenges in moving this work from bench to bedside (Arrieta et al, 2016;Dinan and Cryan, 2016). This includes the fact that the rodent gastrointestinal tract and microbiota composition differs from the human equivalent (Nguyen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the momentum provided by preclinical microbiome studies, there is a growing appreciation of the challenges in moving this work from bench to bedside (Arrieta et al, 2016;Dinan and Cryan, 2016). This includes the fact that the rodent gastrointestinal tract and microbiota composition differs from the human equivalent (Nguyen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous work shows that, once the new microbiota is established in the new host, its composition changes from the original inoculum 109,111 . Therefore, it would be difficult to make conclusions about the original components of the transferred microbiota.…”
Section: Is Loss Of Lactobacillus Sufficient To Induce Depressive Behmentioning
confidence: 98%
“…Studying germ-free animals has helped us appreciate the importance of the microbiome and the dangers of widespread antibiotic treatment. This model has also allowed scientists to selective colonize them with humanderived microbiota and further understand its function in ways that human studies do not allow [109][110][111] . For instance, in one of the first studies of this kind, Smith and colleagues showed that it is poor diet-associated microbiota that drives growth stunting 110 .…”
Section: Human Vs Mouse Microbiomementioning
confidence: 99%
See 2 more Smart Citations